The Effect of Profitability, Liquidity, Company Size, and Institutional Ownership On Earning management In Industrial Sector Companies Listed On The Indonesia Stock Exchange In 2019-2022 - Syafiqoh, Naufal; Rochmatullah, Mahameru Rosy (Dinasti Publisher, 2024)
Earning management is an implementation carried out by the company's management to carry out actions to manipulate financial statements in order to achieve certain targets. This study was conducted with the aim to find the effect of profitability, liquidity, company size, and institutional ownership on earning management. The population of this study is an industrial sector company listed on the Indonesia Stock Exchange for the period 2019-2022. Sampling techniques using purposive sampling and obtained by 19 companies. Data analysis using multiple linear regression. The results showed that profitability measured using Return on Assets has no effect on earning management, Net Profit Margin has an effect on earning management, Return on Equity has an effect on earning management. Liquidity as measured by The Current Ratio, Quick Ratio, and Cash Ratio does not affect earning management. The size of the company is measured by the natural logarithm of total assets resulting in the size of the company has an affects earning management. Institutional ownership is measured by the division between the ownership of the number of shares of the institution and the number of shares outstanding, resulting in that institutional ownership has no effect on earning management. High and low return on assets, liquidity, and institutional ownership have no effect on earning management. But the higher the value of net profit margin, return on equity, and company size in a company, the lower the value of earning management. Conversely, the lower the value of net profit margin, return on equity, and company size, the value of earning management value increases.